Concurrent Primary Aldosteronism and Renal Artery Stenosis: An Overlooked Condition Inducing Resistant Hypertension - Zhao, Lin; Xue, Jinhong; Zhou, Yi; Dong, Xueqi; Luo, Fang; Jiang, Xiongjing; Du, Xinping; Zhou, Xianliang; Meng, Xu (Frontiers in Cardiovascular Medicine, 2022)
To explore the clinical features of coexisting primary aldosteronism (PA) and renal artery stenosis (RAS), we retrospectively analyzed records from 71 patients with PA with RAS and a control group of 121 patients with PA without RAS. Aldosterone-to-renin concentration ratio tests and computerized tomography (CT) scanning of the adrenal and renal arteries were routinely conducted to screen for PA and RAS. Color Doppler flow and/or magnetic resonance imaging were used as substitute testing of patients for whom CT was contraindicated. Standard percutaneous renal arteriography (PTRA) was considered for patients with RAS exceeding 70% based on non-invasive tests and for those without PTRA contraindications. The patients with PA with RAS were further divided into severe (RAS>70%) and moderate (50%< RAS <70%) RAS groups. The prevalence of RAS among PA patients was 6.9% (71/1033), including 3.2% (33/1033) with severe RAS. Compared with the PA without RAS group, the severe RAS group showed higher levels of systolic blood pressure (SBP) (171.82 ± 18.24 vs. 154.11 ± 18.96 mmHg; P < 0.001) and diastolic BP(DBP) (110.76 ± 15.90 vs. 91.73 ± 12.85 mmHg; P < 0.001) and prevalence of resistant hypertension (RH) (90.9% vs. 66.9%; P = 0.008), whereas the moderate RAS group merely showed higher DBP (98.63 ± 14.90 vs. 91.73 ± 12.85 mmHg; P = 0.006). The direct renin concentrations (DRCs) (5.37 ± 3.94 vs. 3.71 ± 2.10 μU/mL; P < 0.001) and false-negative rate (33.8% vs. 3.3%; P < 0.01) of PA screening tests were significantly higher in the PA with RAS group than in the control group, but only in severe RAS group, in subgroup analysis. Among patients who underwent successful treatment for severe RAS, mean DRC decreased from 11.22±9.10 to 3.24±2.69 μIU/mL (P<0.001). Overall, the prevalence of RH decreased from 81.7% to 2.8% (P< 0.001) when both PA and RAS were treated with standard methods. PA with concurrent severe RAS is a condition that induces RH. PA can be easily missed in patients with coexisting RAS. RAS patients with RH after successful revascularization for RAS should be evaluated for coexisting PA.